Non-destructive modulus testing and performance evaluation for asphalt pavement reflective cracking mitigation treatments - Can Chen; Shibin Lin; Ronald Christopher Williams; Jeramy Curtis Ashlock (The Baltic Journal of Road and Bridge Engineering)
Reflective cracking is a common type of pavement distress, which manifests as cracks in an underlying layer propagating through to the surface of a pavement structure. To minimize reflective cracking of asphalt layers in composite pavements, four treatments are commonly used: standard/full rubblization, modified rubblization, crack and seat, and rock interlayer. The four types of treatment were evaluated to determine their effectiveness in mitigating reflective cracking via non-destructive Falling Weight Deflectometer tests and Surface Wave Method tests to measure layer modulus, along with field pavement performance surveys. It is found that moduli measurements from Surface Wave Method tests have reduced uncertainty comparing to those from Falling Weight Deflectometer tests, (2) the moduli of thin rock interlayers were captured by Surface Wave Method, but missed by Falling Weight Deflectometer. In addition, the Surface Wave Method results show that (1) crack and seat treatments provide the highest moduli, followed by modified rubblization, and (2) standard rubblization and rock interlayers provide moduli that are slightly lower than the other two treatments. Pavement performance survey was also conducted concurrently with the in-situ modulus tests. Based on the results of this study, modified rubblization and rock interlayer treatments are recommended for mitigation of reflective cracking.